Relevansi pemikiran moderat Yusuf Al-Qardlawi dengan metode dakwah Habib Husein Ja’far Al-Hadar dalam tayangan Log In di era digitalisasi - Mahmudah, Ni'matul (Maliki Interdisciplinary Journal, 2024)
In this digital era, the dissemination of Islamic preaching has undergone significant transformation. Social media and digital platforms have become new means for preachers to convey Islamic teachings to a wider audience. One figure who effectively utilizes digital media is Habib Husein, who engages with various platforms. In this regard, the moderate thinking of Yusuf Al-Qardlawi, which emphasizes a moderate attitude, is an aspect that needs to be studied and then related to the preaching methods used by Habib Husein, particularly in the LOG IN program. This research aims to examine the relevance of Yusuf Al-Qardlawi's moderate thoughts with the da'wah (Islamic preaching) methods employed by Habib Husein in the LOG IN show during the digital era. Yusuf Al-Qardhawi's moderate thoughts offer a balanced, tolerant, and adaptive understanding of Islamic teachings in the contemporary context. Meanwhile, Habib Husein is a popular preacher who utilizes digital media, particularly the LOG IN show, to spread Islamic teachings with a moderate and contextual approach. This research employs a qualitative approach with a case study method to analyze the LOG IN show in-depth and relate it to Yusuf Al-Qardlawi's moderate thought concepts. Data collection will be conducted through literature studies and documentation related to the research topic. Thematic analysis will be used to identify patterns and themes relevant to the research objectives. The findings of this research are expected to provide a comprehensive understanding of the relevance of moderate thoughts in the context of da'wah in the digital era. The findings of this research are expected to provide a comprehensive understanding of the relevance of moderate thoughts in the context of da'wah (Islamic preaching) in the digital era, as well as how preachers can adapt their da'wah methods to align with technological advancements and the needs of modern society.